Paying the tab the economics of alcohol policy - Cook, Philip J. 1946- (Princeton Univ. Press, 2007)
Publisher description for Paying the tab : the economics of alcohol policy / Philip J. Cook. What drug provides Americans with the greatest pleasure and the greatest pain? The answer, hands down, is alcohol. The pain comes not only from drunk driving and lost lives but also addiction, family strife, crime, violence, poor health, and squandered human potential. Young and old, drinkers and abstainers alike, all are affected. Every American is paying for alcohol abuse. Paying the Tab, the first comprehensive analysis of this complex policy issue, calls for broadening our approach to curbing destructive drinking. Over the last few decades, efforts to reduce the societal costs--curbing youth drinking and cracking down on drunk driving--have been somewhat effective, but woefully incomplete. In fact, American policymakers have ignored the influence of the supply side of the equation. Beer and liquor are far cheaper and more readily available today than in the 1950s and 1960s. Philip Cook's well-researched and engaging account chronicles the history of our attempts to "legislate morality," the overlooked lessons from Prohibition, and the rise of Alcoholics Anonymous. He provides a thorough account of the scientific evidence that has accumulated over the last twenty-five years of economic and public-health research, which demonstrates that higher alcohol excise taxes and other supply restrictions are effective and underutilized policy tools that can cut abuse while preserving the pleasures of moderate consumption. Paying the Tab makes a powerful case for a policy course correction. Alcohol is too cheap, and it's costing all of us.
Includes bibliographical references and index
Keywords: Accijnzen; Alcoholische dranken; Drankbestrijding; Economische politiek; Overheidsbeleid; Politik; Steuer; Wirtschaftspolitik; Alcoholism -- Government policy -- United States; Alcoholism -- United States -- Prevention; Alcoholic beverages -- Taxation -- United States; Alkoholmissbrauch; Prävention; Alkoholismus; Verenigde Staten; USA